Corporate Governance And Directors’ Remuneration In Malaysian Public Listed Companies - Hasnah, Haron; Lok, Char Lee; Chong, Meng Fong (Malaysian Institute of Corporate Governance, 2016)
Over the past decade, the issue of compensation for top executives has been the subject of empirical research due to agency problems that might be manifested as a result of separation of ownership and control. Research into how executives are rewarded caught wide public interest in the Western countries and now has also captured the attention of Malaysians. This is more apparent particularly after a series of financial crises.